Correlation of the Shopee Twin Date Festival on Impulsive Buying Behavior of Gen Z, Ngabang District - Dewi, Karolina (ILTIZAM Journal of Shariah Economics Research, 2024)
The widespread use of e-commerce platforms makes it easy for users to fulfill their needs. One of them is Shopee, the marketing strategy is carried out by holding twin date festivals. This phenomenon can trigger impulsive buying behavior, especially Gen Z. Therefore, this research aims to identify whether there is a correlation between the twin date festival held by Shopee and impulsive buying behavior, especially Gen Z in Ngabang District. This research method uses quantitative analysis with calculations using the SPSS version 29 program. Data collection techniques involve distributing questionnaires, observation and documentation. Questionnaires were distributed to 100 respondents who were the samples in this study. The research results showed that there was a correlation between the Shopee festival date and impulsive buying behavior among Gen Z in Ngabang District. A significance value of 0.001 < 0.05 was obtained, with a Pearson correlation value of 0.554, which means the degree of relationship between the two variables is in the medium category. The form of relationship between the two variables is positive, where the more often Shopee holds twin date festivals, the higher the impulsive buying behavior among Gen Z in Ngabang District.